Subungual melanoma. Diagnostic and treatment problem - Łoziński, Cezary; Wojnerowicz, Czesław; Teresiak, Ewa; Teresiak, Marek; Karpisiewicz, Małgorzata; Kycler, Witold (Contemporary Oncology/Współczesna Onkologia, 2003)
The aim of this study is to evaluate subungual melanoma as a site-specific entity, to document its natural history, and to evaluate diagnostic and treatment modalities. From 1953 to 2001, 1714 patients were operated because of melanoma in the Wielkopolska Oncology Centre in Poznań in the Department of Oncological Surgery (1953–1988) and in The Second Department of Oncological Surgery (1988–2001). These included 19 subungual lesions. The mean age was 58 years (aged 37–70). The nails were affected in 19 cases: great toe’s nails in 10 cases (52.6%), the thumb’s nails in 7 cases (36.8%), the ring finger’s nails in 1 case (5.3%) and V finger’s nails in 1case (5.3%). 16 patients (84.2%) were misdiagnosed as having traumatic, infective or benign lesions. In all cases the diagnosis was confirmed by histopathological examination. Regional lymph nodes were affected in 17 patients (89.5%). All patients underwent amputation of the involved digit and 15 (78.9%) required node dissection (13 patients had pathologically positive lymph nodes). Two patients (10.5%) are alive, 1 is disease-free and 1 has metastases. Subungual melanoma is a relatively rare disease with characteristic clinicopathologic signs. Delayed diagnosis and advanced disease at presentation contribute to the poor prognosis in nail bed melanoma.